2009
DOI: 10.1614/ws-08-112.1
|View full text |Cite
|
Sign up to set email alerts
|

Red Rice (Oryza sativa) Emergence Characteristics and Influence on Rice Yield At Different Planting Dates

Abstract: Cultivated rice yield losses due to red rice infestation vary by cultivar, red rice density, and duration of interference. The competition effects of red rice could be influenced further by emergence characteristics, red rice biotype, and planting time of cultivated rice. We aimed to characterize the emergence of red rice biotypes at different planting dates and evaluate the effect of red rice biotype, rice cultivar, and planting date on cultivated rice yield loss. Field experiments were conducted at the South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 32 publications
1
45
0
7
Order By: Relevance
“…The highest plant height and tiller number (90.08 ± 12.32 cm and 3.70 ± 1.42, respectively) were found in transplanted weedy rice variants with no competition while the lowest plant height (55.88 cm) and tiller number (2.08) were observed in improved rice in DSP interacting with weeds. Shivrain et al (2009) reported that 12 ecotypes of weedy rice produced 226 to 462 tillers m -2 while the cultivar of inbred rice produced 250 tillers m -2 in a competition of 1/19 weedy vs. rice. The effects of weed density on rice growth, higher tillering capacity, and shoot development potential of weedy rice generally decreases grain yield in rice production.…”
Section: Weedy Rice Biology and Competition With Cultivated Ricementioning
confidence: 99%
“…The highest plant height and tiller number (90.08 ± 12.32 cm and 3.70 ± 1.42, respectively) were found in transplanted weedy rice variants with no competition while the lowest plant height (55.88 cm) and tiller number (2.08) were observed in improved rice in DSP interacting with weeds. Shivrain et al (2009) reported that 12 ecotypes of weedy rice produced 226 to 462 tillers m -2 while the cultivar of inbred rice produced 250 tillers m -2 in a competition of 1/19 weedy vs. rice. The effects of weed density on rice growth, higher tillering capacity, and shoot development potential of weedy rice generally decreases grain yield in rice production.…”
Section: Weedy Rice Biology and Competition With Cultivated Ricementioning
confidence: 99%
“…Entretanto, nessa mesma condição, o biótipo 3 apresentou similaridade ao genótipo de arroz, demonstrando que há diferenças no comportamento de biótipos de arroz-vermelho. Estudo realizado por Shivrain et al (2009), também constataram variação de emergência entre biótipos de arroz-vermelho em diferentes épocas de semeaduras do arroz irrigado.…”
Section: Resultsunclassified
“…O controle do arroz-vermelho torna-se dificultado devido a similaridade fisiológica com o arroz cultivado (SCHWANKE et al, 2008), e devido a diversidade de biótipos com características morfológicas distintas presentes em uma população de arroz-vermelho (FONTANA et al, 2007;MENEZES et al, 2002;SHIVRAIN et al, 2009).…”
Section: Introductionunclassified
See 2 more Smart Citations